Mining of a phospholipase D and its application in enzymatic preparation of phosphatidylserine. Issue 1 (1st January 2018) - Zhou, Wen-Bin; Gong, Jin-Song; Hou, Hai-Juan; Li, Heng; Lu, Zhen-Ming; Xu, Hong-Yu; Xu, Zheng-Hong; Shi, Jin-Song
ABSTRACT: Phosphatidylserine (PS) is useful as the additive in industries for memory improvement, mood enhancement and drug delivery. Conventionally, PS was extracted from soybeans, vegetable oils, egg yolk, and biomass; however, their low availability and high extraction cost were limiting factors. Phospholipase D (PLD) is a promising tool for enzymatic synthesis of PS due to its transphosphatidylation activity. In this contribution, a new and uncharacterized PLD was first obtained from GenBank database via genome mining strategy. The open reading frame consisted of 1614 bp and potentially encoded a protein of 538-amino-acid with a theoretical molecular mass of 60 kDa. The gene was successfully cloned and expressed in Escherichia coli . Its enzymatic properties were experimentally characterized. The temperature and pH optima of PLD were determined to be 60°C and 7.5, respectively. Its hydrolytic activity was improved by addition of Ca 2+ at 5 mM as compared with the control. The enzyme displayed suitable transphosphatidylation activity and PS could be synthesized with L -serine and soybean lecithin as substrates under the catalysis of PLD. This PLD enzyme might be a potential candidate for industrial applications in PS production. To the best of our knowledge, this is the first report on genome mining of PLDs from GenBank database.